Clinical presentation and molecular basis of congenital antithrombin deficiency in children: a cohort study. (29th March 2014) - Kumar, Riten; Chan, Anthony K. C.; Dawson, Jennifer E.; Forman‐Kay, Julie D.; Kahr, Walter H. A.; Williams, Suzan
Summary In this study we report the largest descriptive cohort of congenital antithrombin (AT) deficiency in children, its clinical presentation, molecular basis and genotype‐phenotype correlation. Paediatric patients diagnosed with AT deficiency at two tertiary care children's hospitals over a 10‐year period were retrospectively reviewed. SERPINC1 gene sequencing was offered to subjects who did not already have the test performed. Molecular modelling and stability simulations were performed for the novel mutations identified. Twenty‐nine subjects from 18 pedigrees were identified. Mean age (± standard deviation) at diagnosis and mean duration of follow‐up were 8·4 (± 6·6) years and 6·6 (± 5·7) years respectively. Most recent mean AT activity and AT antigen levels (n = 20) were 0·53 (± 0·09) iu/ml and 0·60 (± 0·17) iu/ml respectively. Ten subjects were diagnosed secondary to low AT activity measured following venous thrombo‐embolism (VTE). All 10 subjects had additional risk factors at the time of VTE. None of the 19 subjects diagnosed with AT deficiency in the setting of positive family history have had VTE with 7·4 (± 5·8) years follow‐up. Mutation analysis has been completed on 19 subjects from 16 pedigrees. Nine unique mutations, including 4 novel mutations were identified.